Does women's empowerment affect the health of children? The case of Mozambique - Joseph Deutsch; Jacques Silber (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
In developing countries, women's decisions concerning their children's health depend on `empowerment' concerning decision-making, husband/partner's use of violence, woman's attitude towards this violence, available information, and resources. We derive an empowerment indicator using the `fuzzy sets' and Alkire and Foster approaches to multidimensional poverty measurement. The health of children is a latent variable; their height and weight are observed health indicators. We apply the `MIMIC' approach to the 2009 Mozambique Demographic and Health Survey. Children's health is better when the woman opposes her partner's violence, the higher her education and body mass index, among female children, and in urban areas.
Keywords: D13; J16; O55; 330; Alkire and Foster; Demographic and Health Survey; fuzzy approach to poverty measurement; health; Mozambique; women's empowerment